Resource Usage and Optimization Opportunities in Workflows of GitHub Actions - Bouzenia, Islem; Pradel, Michael (Proceedings / International Conference on Software Engineering, 2024)
Continuous integration and continuous delivery (CI/CD) has become a prevalent practice in software development. GitHub Actions is emerging as a popular platform for implementing CI/CD pipelines, called workflows, especially because the platform of-fers 2,000 minutes of computation for free to public repositories each month. To understand what these resources are used for and whether CI/CD could be more efficient, this paper presents the first comprehensive empirical study of resource usage and optimization opportunities of GitHub Action workflows. Our findings show that CI/CD imposes significant costs, e.g., 504 per year for an average paid-tier repository. The majority of the used resources is consumed by testing and building (91.2%), which is triggered by pull requests (50.7%), pushes (30.9%), and regularly scheduled workflows (15.5%). While existing optimizations, such as caching (adopted by 32.9% of paid-tier repositories), demonstrate a positive impact, they overall remain underutilized. This result underscores the need for enhanced documentation and tools to guide develop-ers toward more resource-efficient workflows. Moreover, we show that relatively simple changes in the platform, such as deactivating scheduled workflows when repositories are inactive, could result in reductions of execution time between 1.1% and 31.6% over the impacted workflows. Overall, we envision our findings to help improve the resource efficiency of CI/CD pipelines.